A real‐world efficacy and safety analysis of combined carfilzomib, lenalidomide, and dexamethasone (KRd) in relapsed/refractory multiple myeloma. Issue 1 (1st November 2020) - Rocchi, Serena; Tacchetti, Paola; Pantani, Lucia; Mancuso, Katia; Rizzello, Ilaria; di Giovanni Bezzi, Chiara; Scalese, Marco; Dozza, Luca; Marzocchi, Giulia; Martello, Marina; Barilà, Gregorio; Antonioli, Elisabetta; et al.
Abstract: Carfilzomib–lenalidomide–dexamethasone (KRd) has been approved for the treatment of relapsed/refractory multiple myeloma (RRMM). We conducted a retrospective analysis of 197 RRMM patients (pts) between January 2016 and March 2018 in six Italian hematologic centers, with the aim to evaluate efficacy and safety of KRd in real‐life. At KRd initiation 27% carried high risk cytogenetic abnormalities (HRCA) [del17p and/or t(4;14) and/or t(14;16)], median number of prior lines of therapy was 2 (1–8), nearly all pts (96%) received prior bortezomib (18% refractory) while 45% were exposed to lenalidomide (R; 22% refractory). At the median of 12.5 months, 52% of the pts had discontinued treatment, mainly (66%) for progression. Main grade 3–4 adverse events were neutropenia (21%), infections (11%), and hypertension (6%). Overall, the response rate was 88%. The median progression‐free survival (PFS) was 19.8 months and 1‐year overall survival (OS) rate was 80.6%. By subgroup analysis, extended PFS and OS were observed for pts who received ≤2 prior lines of therapy (HR = 0.42, p < 0.001 and HR = 0.35, p = 0.001, respectively), not refractory to prior R (HR = 0.37, p < 0.001, and HR = 0.47, p = 0.024), without HRCA (HR = 0.33, p = 0.005 and HR = 0.26, p = 0.016) and achieving ≥ very good partial response (VGPR; HR = 0.17, p < 0.001 and HR = 0.18, p < 0.001). In conclusion, KRd demonstrated to be effective in RRMM pts treated in real‐world setting, without new safety concerns. Better survival outcomes emerged for pts with ≤2 prior lines of therapy, achieving at least a VGPR, and without HRCA.